Parenting Patterns in the Digitalization Era: A Sociological Study on the Role of Families in RT 002/001 Amantelu, Ambon - Selina Margarita Manuhutu; Feky Manuputty; Dominggus E.B. Saija (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2026)
This study examines parenting patterns in the era of digitalization through a sociological perspective on the role of families in RT 002/001 Amantelu, Ambon. The research aims to analyze how parents adapt their parenting practices to the rapid development of digital technology and how these changes influence children’s social behavior, communication patterns, and family relationships. The study employs a qualitative descriptive method using observation, in-depth interviews, and documentation techniques involving parents, children, and community figures as research participants. Data were analyzed through data reduction, categorization, interpretation, and conclusion drawing to identify the dominant patterns of parenting in the digital era. The findings reveal that digitalization has transformed family interaction patterns by increasing children’s exposure to smartphones, social media, and online entertainment. Parents apply various parenting approaches, including democratic, permissive, and protective patterns, depending on their educational background, economic condition, and level of digital literacy. The study also shows that families play a strategic role in controlling digital consumption, instilling moral values, and maintaining social cohesion within the household. However, limited parental supervision and unequal digital understanding among family members often create challenges such as reduced face-to-face interaction, children’s dependence on digital devices, and weakened social control within the family environment. The novelty of this study lies in its sociological analysis of parenting practices in a local urban community in Ambon, highlighting the intersection between digital transformation, family adaptation, and community-based social values. The study concludes that effective parenting in the digital era requires adaptive communication, digital literacy, and collaborative family supervision to balance technological advancement with children’s social and moral development. This research recommends strengthening family-based digital education programs and community socialization initiatives to support parents in developing responsive and socially oriented parenting practices in the digital age.